2019
DOI: 10.1021/acs.jmedchem.9b01113
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Potent, Selective, and Orally Available MTHFD2 Inhibitor (DS18561882) with in Vivo Antitumor Activity

Abstract: We report the discovery of a potent and isozyme-selective MTHFD2 inhibitor, DS18561882 (2). Through investigation of the substituents on our tricyclic coumarin scaffold (1,2,3,4-tetrahydrochromeno­[3,4-c]­pyridin-5-one), MTHFD2 inhibitory activity was shown to be elevated by incorporating an amine moiety at the 8-position and a methyl group at the 7-position of the initial lead 1. X-ray structure analysis revealed that a key interaction for enhanced potency was salt bridge formation between the amine moiety an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(89 citation statements)
references
References 16 publications
2
86
0
Order By: Relevance
“…With extended MTHFD2i treatment of 48 hours, these purine products were only depleted in Th17 cells and not Th1 or Treg cells ( Figure 6F and G). This finding was reproduced with a second MTHFD2i (Kawai et al, 2019) (Supplemental Figure 2A). These changes were sufficient to reduce proliferation, as media supplemented with adenine and guanine was sufficient to rescue cell numbers in MTHFD2itreated Th17 cells ( Figure 6H).…”
Section: Mthfd2 Activity Regulates Mtorc1 Activity In Th1 and Treg Cesupporting
confidence: 55%
See 1 more Smart Citation
“…With extended MTHFD2i treatment of 48 hours, these purine products were only depleted in Th17 cells and not Th1 or Treg cells ( Figure 6F and G). This finding was reproduced with a second MTHFD2i (Kawai et al, 2019) (Supplemental Figure 2A). These changes were sufficient to reduce proliferation, as media supplemented with adenine and guanine was sufficient to rescue cell numbers in MTHFD2itreated Th17 cells ( Figure 6H).…”
Section: Mthfd2 Activity Regulates Mtorc1 Activity In Th1 and Treg Cesupporting
confidence: 55%
“…To test the role of MTHFD2 in CD4 T cell subset activation, differentiation, proliferation, and function, CD4 cells were activated in vitro in the presence of cytokines for optimal Th1, Th17, and Treg differentiation together with vehicle or an MTHFD2 inhibitor (MTHFD2i; DS18561882) (Kawai et al, 2019). After 72 hours of incubation with the inhibitor, all subsets were found to have significantly reduced cell numbers, although only Th17 cells had statistically significantly reduced viability ( Figure 3A).…”
Section: Cd4 T Cell Subsets Differentially Require Mthfd2mentioning
confidence: 99%
“…In vitro and in vivo experiments of NSCLC indicated that knockdown of MTHFD2 can reduce cell growth and tumorigenicity [26]. Kawai et al [27] reported that DS18561882, an MTHFD2 inhibitor, has a strong antitumor effect on mouse xenograft model. In the present study, the mRNA and protein expressions of MTHFD2 were higher in EC tissues than in normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…185 Besides, other MTHFD2 inhibitors have been reported, including DS18561882 and LY345899 in a substrate-based manner, and treatments based on them decrease cellular NADPH/NADP + ratio, increase cellular ROS levels, and impair tumorigenesis and metastasis. 74,186 For the glutamine metabolism pathway, ebselen, epigallocatechin-3-Gallate (EGCG), and propylselen are reported to bind to GDH-active sites to abolish NADP + binding and impair in cancer cell functions. 187 A study also shows that purpurin and its analog, R162, acting as mixed model inhibitors of GDH1, inhibit GDH1 activity, elevate ROS levels and thus attenuate cancer cell proliferation.…”
Section: Fatty Acid Oxidationmentioning
confidence: 99%
“…Cell Biol. 17, 1484–1496 (2015) MTHFDs LY345899 Colorectal cancer 10 μM ~12 μM (SW620, 72 h) >200 μM (CCD-112, 72 h) 74 MTHFD2 DS18561882 Breast cancer 140 nM 140 nM (MDA-MB-231, 24 h) Not available 186 GDHs Propylselen Lung cancer cells 0–10 μM 3.4 μM (A549, 48 h) Not available 187 R162 Non-small cell lung carcinoma 20–40 μM 10 μM (KG1a, 48 h) >40 μM (MRC-5, HFF, 48 h) 151 IDH1 GSK864 Glioma 5–100 μM 5 μM (LN382, 48 h) Not available 125 IDH2 AGI-6780 Non-small cell lung carcinoma 0–50 μM ~5 μM (A549, 24 h) >50 μM (MRC-5, 48 h) 134 ME1 Piperazine-1-pyrrolidine-2,5-dione Colorectal cancer 50 μM <50 μM (HCT116, 24 h) >50 μM (IEC6, 24 h) 90 ME2 Embonic acid Non-small cell lung carcinoma 1–10 μM 1.4 μM (H1299, 48 h) Not available 189 CPTs Perhexiline Colorectal cancer 10–40 μM <20 μM (HCT116, 24 h) >20 μM (CCD841, 24 h) 167 CPT1 Etomoxir Prostate cancer 50–200 μM <75 μM (VCaP, 48 h) >75 μM (BPH-1, 48 h) Mol. Cancer Ther.…”
Section: Therapeutic Implications For Targeting Nadph Metabolismmentioning
confidence: 99%